BRANCH RETINAL ARTERY OCCLUSION WITH PARACENTRAL ACUTE MIDDLE MACULOPATHY PRESUMABLY RELATED TO HEAVY CANNABIS USE. Issue Volume 16:Issues 4(2022) (July 2022) - Ramtohul, Prithvi; Freund, K. Bailey; Sarraf, David
Abstract : A 21-year-old healthy man presented with branch retinal artery occlusion and paracentral acute middle maculopathy on optical coherence tomography. Subsequent workup for systemic associations was unremarkable, except for heavy cannabis consumption. His clinical presentation and multimodal imaging findings are described. Abstract : Purpose: To report a case of branch retinal artery occlusion associated with paracentral acute middle maculopathy on spectral-domain optical coherence tomography presumably related to heavy cannabis consumption. Methods: Retrospective case report. Spectral-domain optical coherence tomography, fluorescein angiography, and optical coherence tomography angiography were performed. Results: A 21-year-old healthy man described the acute onset of superior visual field loss in his right eye. He admitted smoking approximately 15 g daily of cannabis for several weeks during COVID-19 confinement. Ophthalmoscopic examination of the right eye showed inferotemporal retinal whitening. Spectral-domain optical coherence tomography illustrated evidence of the ischemic cascade with diffuse hyperreflectivity of the inner and middle retinal layers within the central region of the retinal infarct and paracentral acute middle maculopathy at the border of the infarct. Optical coherence tomography angiography demonstrated predominant flow signal loss at the level of the deep retinal capillary plexus. Fluorescein angiography and complete systemic workup were unremarkable. Conclusion: Branch retinal artery occlusion and paracentral acute middle maculopathy may be related to heavy cannabis use as the result of transient arterial vasospasm.